Comparative study on skills needed by organizations and effectively developed in eLearning management courses - Sousa, M.; González-Loureiro, M. (Universal Access in the Information Society, 2017)
This paper investigates the skills developed in higher education management courses through an eLearning process. The relevance of this research is based on the approach to theories of skills development, and the main purpose is to identify the skills developed by the students from management courses and compare it to the skills needed by the organizations to be competitive in the market. In this stage of the research, the skills needed by the organizations were identified through a document analysis of prospective studies conducted in industrial sectors developed in the last 15 years. In order to verify whether these skills are developed in the management courses, an online survey was conducted among distance learning University students from 2011 to 2014. The research problem considered the analytical dimension of skills development in organizations anchored to the following research questions: What were the skills identified in the prospective studies? What has been the level of skills developed in courses on management in e-learning mode in higher education? What were the relationships between the perceived skills development and various factors such as gender, employed/unemployed, type of organization and job variables? What are the lessons learnt in order to propose a theoretical model developing skills in higher education management courses? This study is centred on the research of more relevant work skills which can contribute to organizations’ performance and competitiveness in the market.